The Effects of Green Innovation, Eco-Efficiency, Business Strategy, Technology Information Investment, and Profitability on Firm Value - David Silaban; R.Rosiyana Dewi (Yayasan Ilomata, 2023)
The current economic growth is in line with the increase in the number of business units and the growth in the number of business units is believed to not only have positive but also the negative effects on the environment and the earth. For this reason, current investment decisions by stakeholders are also seen from the company's effort and contribution to the environmental improvement. This study aims to determine the effects of green innovation, eco-efficiency, business strategy, information technology investment, and profitability on firm value in companies listed on the Indonesia Stock Exchange. In this research, the sources are taken from the annual report, sustainability report and information on the company website. The research sample comprising 125 companies that met the criteria and are listed on the Indonesia Stock Exchange in 2019-2021. The sampling technique used was purposive sampling and the hypothesis testing in this study is multiple linear regression analysis. The results of this study indicate that cost leadership strategy and profitability have a positive effect on firm value. while green innovation, eco-efficiency, differentiation strategy, and information technology investment have no effect on firm value.